PENGARUH BUDAYA ORGANISASI TERHADAP PRESTASI KERJA KARYAWAN TRANSERA HOTEL PONTIANAK - Galasius Galasius; Aminuyati Aminuyati; Khosmas Khosmas (Universitas Tanjungpura, 2019)
AbstractThis study was aimed to determine the effect of organizational culture on the work performance of employees of Transera Hotel Pontianak. This research was an ex post facto study with a quantitative (associative) approach. The variables in this study were organizational culture, and work performance. The data source in this study was Transera Hotel Pontianak employees. This study used samples with census technique. Research data was collected through questionnaires and documentations. Data analysis was carried out by simple linear regression analysis. Through simple regression analysis showed that there is a positive and significant influence of organizational culture on the work performance of employees of Transera Hotel Pontianak, with a calculated of 9,494 and a significance of 0,000. The results of the determinant coefficient was 0.530, indicating that organizational culture has an effect of 53% on the work performance of Transera Hotel Pontianak employees.Keywords: Organizational Culture, Work Achievement.